Pengaruh Status Gizi terhadap Erupsi Gigi Molar Pertama Permanen Siswa Kelas 1 SDN di Kecamatan Wilayah Kota Administrasi Jember (The Influence of Nutritional Status towards the First Permanent Molar Tooth Eruption Among 1st Grade Students in Jember - Fakhirouz Zakiyah; Dwi Prijatmoko; Masniari Novita (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Background: Tooth eruption is a continuos processes where the teeth grow, develop, and erupt. These processes were affected by many factors, such as nutritional status which can be examined by anthropometry assessment. Many studies have been conducted to understand the relationship between nutritional status and tooth eruption, how ever study associated with the relation of nutritional status and the eruption of first permanent molars in Jember district area has never been done before. Purpose: To determine the influence of nutritional status towards the number of the first permanent molar tooth eruption among 1st grade students in Jember district area. Methods: This is analytic observational study with a cross sectional approach. We used stratified random sampling technique and 238 1st grade students were participate as volunteers. The nutritional status was assessed by Adolphe Quetelet (BMI) formula corrected for age. Intraoral examination was conducted to count the number of the first permanent molar tooth eruption. The data was analyzed using chi-square. Result: There is significant difference between the first permanent molar tooth eruption and nutritional status among 1st grade students in Jember district area (p = 0,000). Conclusion: Nutritional status has significant influence the number of the first permanent molar teeth eruption. Keywords: nutritional status, tooth eruption.